(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
There are several key factors in developing the thinking skills of preschool children. This article analyzes the main factors influencing the formation and development of children’s thinking, such as games, creative activities, experiences, and environmental influences. Additionally, it highlights the importance of speech, emotional environment, and interactive approaches in stimulating children’s thought processes.